SOX combined with tislelizumab and low-dose radiation therapy for the neoadjuvant treatment of locally advanced gastric/gastroesophageal junction adenocarcinoma: study protocol for a prospective, multicenter, single-arm, phase Ib/II clinical trial - Zhang, Peng-Fei; Chen, Ye; Li, Wen-Ke; Luo, Zhu-Mei; Chen, Ji; Qian, Kun; Chen, Xiao-Dong; Wang, Mo-Jin; Liu, Ming (Frontiers in Immunology, 2024)
BackgroundRecently, the clinical benefits of neoadjuvant chemotherapy combined with immunotherapy have been observed in patients with locally advanced gastric or gastroesophageal junction (G/GEJ) cancer; however, the pathological complete response (pCR) and long-term survival rates are still unsatisfactory. The aim of this study is to investigate the efficacy and safety of chemotherapy combined with tislelizumab and low-dose radiation therapy (LDRT) for the neoadjuvant treatment of locally advanced G/GEJ cancer.MethodsThis is a prospective, multicenter, single-arm, phase Ib/II trial. In the phase Ib study, 5 patients will be enrolled in each treatment group with different radiation doses. In the phase II study, a total of 44 patients will be enrolled. Eligible patients will be registered and receive three cycles of SOX regimen chemotherapy (S-1: 40-60 mg Bid, d1-14, q3w; oxaliplatin: 130 mg/m2, iv drip, d1, q3w) plus tislelizumab (200 mg, iv drip, d1, q3w). Simultaneously, LDRT will be planned and administered after the first cycle of systemic therapy. Radical D2 gastrectomy will be performed 4-6 weeks after the last administration of chemotherapy plus tislelizumab. The primary endpoint of phase Ib study is to determine the optimal radiation dose for phase II study. The primary endpoint of phase II is the pCR rate. The secondary endpoints include R0 resection rate, major pathological response (MPR) rate, 2-year event-free survival (EFS) rate, 2-year overall survival (OS) rate and safety profile. Moreover, we will also explore potential molecular markers for predicting the benefit and safety of this neoadjuvant regimen. Written informed consent should be provided by all patients enrolled in the study. The study protocol was approved by the independent ethics committee at each institution.DiscussionThis is the first study to explore the efficacy and safety of neoadjuvant chemotherapy combined with tislelizumab and LDRT in G/GEJ cancer patients, the results of which may provide novel treatment strategy for patients with locally advanced G/GEJ adenocarcinoma.Clinical trial registrationClinicalTrials.Gov, identifier NCT06266871.